Análise do papel da autoavaliação institucional no processo de melhoria da qualidade na Universidade Federal da Paraíba - Souza, Saulo Rodrigo Alves de (2019)
This dissertation aimed to analyze the role of institutional self-assessment in the process of quality improvement at the Federal University of Paraíba (UFPB), based on the results of the last 05 (five) Institutional Self-Assessment Reports (RAAI's) applied by the Evaluation Committee itself. Federal University of Paraíba, in relation to the 2017 Institutional External Assessment Instrument (IAIE), prepared by the National Institute for Educational Studies and Research Anísio Teixeira (INEP) / Ministry of Education (MEC). The present investigation, regarding the approach, was of the qualitative type; as regards nature, applied research; Regarding the objectives, it was an exploratory research; and used as a procedure bibliographic and documentary research. Besides the specific legislation about the evaluation of higher education in Brazil, our theoretical basis was based on the studies of Dilvo Ilvo Ristoff, Jose Dias Sobrinho, Robert Verhine, among others. We use SWOT analysis as a tool to assist in identifying the strengths, weaknesses, opportunities and threats that positively or negatively impact the quality of education within the UFPB. For this investigation, we adopted the conception of quality proposed by SINAES. The results of the study showed that although the UFPB develops annually its self-assessment process and it presents itself in the theoretical field as a relevant instrument of self-knowledge of the weaknesses and potentialities of this IFES, the appropriation of its results to support decision making is still incipient. Moreover, self-assessment in the way it has been conducted does not yet provide an overview of this IFES.